Penerapan Model Teams Games Tournament (TGT) Untuk Meningkatkan Hasil Belajar Pembelajaran Tematik Terpadu Siswa Kelas III A UPTD SDN 66 Kanjitongan - Syarifah Aeni Rahman; Syafaruddin Syafaruddin; Nurul Ihza; Nurhidayana Jamil; Nurlindah Nurlindah (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Based on observation results, student learning outcomes are still low. This research aims to improve student learning outcomes in Integrated Thematic Learning using the Teams Games Tournament (TGT) learning model. This research was carried out at UPTD SDN 66 Kanjitongan, Kanjitongan Hamlet, Mattiro Tasi Village, Maros Baru District, Maros Regency. The subjects of this research were 19 students in class IIIA UPTD SDN 66 Kanjitongan for the 2023/2024 academic year. The type of research used is Classroom Action Research. Based on the research results, it can be concluded that the application of the Teams Games Tournament (TGT) model in Integrated Thematic Learning can improve the learning outcomes of class III A UPTD students at SDN 66 Kanjitongan. This is shown by the results of the analysis in cycle I, the percentage of students who have reached the Minimum Completeness Criteria is 68.42% and the percentage of students who have not reached the Minimum Completeness Criteria is 31.58%. 2 cycles with the percentage of students who have reached the Minimum Completeness Criteria89.47% and the percentage of students who have not reached the Minimum Completeness Criteria 10.53%.